Robust Command Shaped Vibration Control for Stacker Crane Subject to Parameter Uncertainties and External Disturbances - Li, Gang; Ma, Xin; Li, Yibin (IEEE transactions on industrial electronics (1982), 2024)
The payload hoisting and mass variations increase the control difficulty of the underactuated stacker crane. Especially, vibration control of flexible structure with external disturbances is a great challenge. This article proposes a robust command shaped vibration control method for the stacker crane under the external disturbance effect together with the payload hoisting and mass variations. First, we use the Lagrange's method to establish an equivalent dynamic model of the stacker crane with payload hoisting. Then, the robust command shaped vibration control method is designed with piecewise function shaped command and disturbances rejection command. By using the modified neural network estimator, the parameters of the robust command shaper can adapt in real-time according to payload hoisting and mass variations. The vibration of a specified frequency range is suppressed by the piecewise function shaped command, which improves the robustness to the parameter uncertainties. A disturbances rejection command eliminates the vibration of flexible structure resulting from the external disturbances. Finally, the robustness and effectiveness of the proposed method is verified through the experiment. The superiority of the proposed command is confirmed by improvement of at least 24.69% and 68.32% in the maximum and residual vibration deflection, respectively, over the existing shaping control methods.